1999
DOI: 10.1046/j.1365-2249.1999.00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cells in cross-regulation of IL-12 by IL-10 inLeishmaniaantigen-stimulated blood donor cells

Abstract: We have previously shown that natural killer (NK) cells play a role in protection against leishmaniasis. Furthermore, we have shown that NK cells in mononuclear cells derived from unexposed donors are induced to proliferate in vitro in response to leishmanial antigens. Since interleukin (IL)-12, a strong inducer of NK cells, acts on the early events in NK cells and T-cells, and is considered as an adjuvant for use in a potential antileishmaniasis antigen, we wished to investigate how this cytokine influences t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
2
11
0
2
Order By: Relevance
“…Inactivation of MHC class II would result in lowered levels of CD4 ϩ as well as CD16/56 ϩ cells. This model is consistent with our finding that CD16/56 ϩ cells alone cannot be activated by FtLeish Ag but require the presence of other cell types to be preferentially induced to proliferate and secrete cytokines [18]. Our data also show that, in the presence of plastic-adherent cells and in the absence of CD4 ϩ cells, NK cells can secrete high levels of IFN-g in response to LACK stimulation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Inactivation of MHC class II would result in lowered levels of CD4 ϩ as well as CD16/56 ϩ cells. This model is consistent with our finding that CD16/56 ϩ cells alone cannot be activated by FtLeish Ag but require the presence of other cell types to be preferentially induced to proliferate and secrete cytokines [18]. Our data also show that, in the presence of plastic-adherent cells and in the absence of CD4 ϩ cells, NK cells can secrete high levels of IFN-g in response to LACK stimulation.…”
Section: Discussionsupporting
confidence: 92%
“…We have elsewhere shown that NK cells alone cannot be stimulated to proliferate or to secrete IFN-g in our Ft-Leish system [18]. Thus, in the present study, we evaluated the capacity of LACK (a candidate prominent component of the Ft-Leish response in healthy donors) to be stimulatory to NK cells in the presence of adherent cells.…”
Section: Stimulation Of Nk Cells By Lackmentioning
confidence: 92%
“…Similarly, production of IL-10 by monocytes is elevated during the infection with Chlamydia pneumoniae [29]. IL-10 is a cytokine which directly influences NK cells quenching their cytotoxic activity [30]. IL-10 counteracts IL-2 secretion, which results in decrease of NK cell function [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…A low basal level and an elevated circulating IL-6 after IL-2 therapy have been regarded as good indicators of predicting an anticancer response [19]. In contrast, IL-10 is regarded as a potent immunosuppressive factor, which involves in the inhibition of interferon-γ secretion and T cell proliferation after antigen stimulation [20]and plays an important role in the stress-induced immunosuppression [21]. IL-10 is causally involved in dampening the inflammatory response induced by IL-2 [22].…”
Section: Discussionmentioning
confidence: 99%